Jus Apel Manalagi dan Kadar Glukosa Darah Tikus Putih yang Mengalami Hiperglikemia - yuliwar, roni (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2017)
Abstract: The general objective of this research is studying the effect of apple manalagi juice to bloodglucose profiles Rat (Rattus norvegicus) Wistar strain, experiencing hyperglycemia. The study populationwas White Rat (Rattus norvegicus) adult male Wistar strain, taken from the captivity in Malang. Thesample in this study Rats (Rattus norvegicus) Wistar strain adult male weighing 135-200 g, Ã‚Â± 3 monthsold, healthy physical condition, were taken randomly from captivity units, as many as 24 tails weredivided into 4 groups randomly complete (randomized allocation). Animals measured blood glucoselevels (GD) rats were taken at the beginning (for all groups), after induction (for all groups), aftertreatment day 3, 7, 14, 21 and 28 (group 2, 3 and 4). The data is processed by descriptive method andanalyzed using one-way ANOVA Test. These results indicate that administration of apple manalagi juicecan lower blood glucose levels.